Neurometals in the Pathogenesis of Prion Diseases - Kawahara, Masahiro (Int J Mol Sci, 2021)
Prion diseases are progressive and transmissive neurodegenerative diseases. The conformational conversion of normal cellular prion protein (PrP(C)) into abnormal pathogenic prion protein (PrP(Sc)) is critical for its infection and pathogenesis. PrP(C) possesses the ability to bind to various neurometals, including copper, zinc, iron, and manganese. Moreover, increasing evidence suggests that PrP(C) plays essential roles in the maintenance of homeostasis of these neurometals in the synapse. In addition, trace metals are critical determinants of the conformational change and toxicity of PrP(C). Here, we review our studies and other new findings that inform the current understanding of the links between trace elements and physiological functions of PrP(C) and the neurotoxicity of PrP(Sc).